Impact of Regional Development Strategy on the Productivity of Polluting Firms:Evidence From China - Dou, Jianmin; Tao, Zhipeng; Ji, Yongbao (Frontiers in Environmental Science, 2022)
This study aims to study the heterogeneous impact of the China's Western Development Strategy (WDS) on the productivity of different types of firms. Based on the heterogeneous firm model and simulation, this study utilizes the WDS as a quasi-natural experiment and uses the difference-in-difference-in-differences (DDD) method to study the heterogeneous impact on the productivity of polluting and non-polluting firms. The WDS has increased the productivity of polluting firms in the western region by 8.0–12.6%, compared to the central region and non-polluting industries. This phenomenon is the result of the environmental cost effect and the migration effect, but not the result of the Potter effect. In addition, this study shows that the heterogeneity of productivity improvement in state-owned firms, large-scale firms, and firms not located in the acid rain and sulfur dioxide control zones is more significant. The study suggests that it is necessary to implement industry-differentiated regional policies, implement different regional preferential policies for polluting firms, and to strengthen environmental regulations, so as to achieve a win-win situation between firm efficiency improvement and environmental protection.